Kingdom of the Netherlands-Aruba : Statistical Appendix. (IMF Staff Country Reports; Country Report, 2001)
The statistical data on indicators of tourism activity, estimated GDP and components, real GDP, contributions to real GDP growth, changes in the consumer price index, legal minimum wages, summary of trends in public finance, and tax revenue of Aruba are presented in the paper. The data on operational budget of the social insurance bank, government debt, balance- of-payments summary, monetary survey, monetary developments, and changes in sources of broad money with respect to Aruba are also presented.